The Foundation of Communications for Medical Professionals - Harish Wankhede; Dipti Nimje (Achievements and Challenges of Medicine and Medical Science Vol. 13, 2025)
MCI (Medical Council of India) now called NMC (National Medical Council) under Graduate Medical Education Regulations, 2017 has released a Competency Based Medical Education (CBME) Curriculum with one of the aims to create an “Indian Medical Graduate” (IMG) can communicate adequately, sensitively, effectively and respectfully with the patients and their relatives. To fulfil this aim AETCOM (Attitude, Ethics and Communication) module ‘Foundation of Communication’ was included in the syllabus considering the present scenario of increased violence among doctors. It has highlighted the need for better communication among medical professionals as one of the strategies to reduce such incidences of violence. This chapter has focused on various principles of communication, strategies to improve communication and overcome barriers in communication.